Difference in mechanical and energy cost between highly, well, and nontrained runners - Slawinski, J. S.; Billat, V. L. (Medicine & Science in Sports & Exercise, 2004)
INTRODUCTION: Recently it has been shown that endurance training decreases the variability in stride rate. This decrease would lead to a reduction in the mechanical and the energy cost of running. PURPOSE: This study therefore aimed to compare the mechanical and the energy cost of running according to the training status of the runner (highly, well, and nontrained endurance runners). METHODS: The kinetic, potential, and internal mechanical costs (Cke, Cpe, and Cint) were measured with a 3D motion analysis system (ANIMAN3D). The energy cost of running (C) was measured from pulmonary gas exchange using a breath-by-breath portable gas analyser (Cosmed K4b2, Rome, Italy). All the parameters were measured on track, for a speed of 4.84 +/- 0.36 m x s(-1). RESULTS: Highly trained runners did not exhibit significantly lower C compared with well or nontrained runners (4.46 +/- 0.38; 4.33 +/- 0.32; 4.46 +/- 0.46 J x kg(-1) x m(-1), respectively; P = 0.75). However, Cpe was significantly lower in highly and well-trained runners compared with nontrained runners (0.43 +/- 0.07; 0.45 +/- 0.05; 0.54 +/- 0.08 J x kg(-1) x m(-1), respectively; P < 0.05). In contrast, Cint was significantly higher in highly trained runners compared with well and nontrained runners (respectively, 0.80 +/- 0.12; 0.60 +/- 0.09; 0.59 +/- 0.10 J x kg(-1) x m(-1); P < 0.05). CONCLUSION: Although there is a significant difference in Cpe and in Cint between runners of various training status, there is no difference in C. Differences in Cpe and Cint may be associated with the same self-optimizing mechanism that contributes to a reduction in the impact loads during the initial portion of the support phase of the stride.